Prisoners of politics: breaking the cycle of mass incarceration - Barkow, Rachel E. (The Belknap Press of Harvard University Press, 2019)
America has the highest incarceration rate in the world among major nations not because of expert assessments of how to tackle crime, but because of piecemeal emotional reactions in jurisdictions throughout the United States to high-profile crimes and public fear. The results have been predictably bad: policies that bust government budgets and devastate individual lives and communities but do nothing to promote public safety. To break this cycle and get better policies, we can no longer set criminal justice policies based on the whims of the electorate. We should instead follow the model we have used in so many other areas of life that has improved public health and safety by relying on expert knowledge. Prisoners of Politics offers a new institutional framework for addressing criminal justice policy that is designed to rely on data instead of stories, on expertise instead of emotion.--